The Therapeutic Potential of Chemo/Thermotherapy with Magnetoliposomes for Cancer Treatment - Alfonso Toro-Córdova; Monserrat Llaguno-Munive; Rafael Jurado; Patricia Garcia-Lopez (MDPI AG, 2022)
Cancer represents a very grave and quickly growing public health problem worldwide. Despite the breakthroughs in treatment and early detection of the disease, an increase is projected in the incidence rate and mortality during the next 30 years. Thus, it is important to develop new treatment strategies and diagnostic tools. One alternative is magnetic hyperthermia, a therapeutic approach that has shown promising results, both as monotherapy and in combination with chemo- and radiotherapy. However, there are still certain limitations and questions with respect to the safety of the systemic administration of magnetic nanoparticles. To deal with these issues, magnetoliposomes were conceived as a new generation of liposomes that incorporate superparamagnetic nanoparticles and oncological pharmaceuticals within their structure. They have the advantage of targeted and selective drug delivery to the diseased organs and tissues. Some of them can avoid the immune response of the host. When exposed to a magnetic field of alternating current, magnetoliposomes produce hyperthermia, which acts synergistically with the released drug. The aim of the present review is to describe the most recent advances in the use of magnetoliposomes and point out what research remains to be done for their application to chemo-thermal therapy in cancer patients.